OECD Tax Policy Reviews: Lithuania 2022 (OECD Tax Policy Reviews, 2022)
This report is part of the OECD Tax Policy Reviews publication series. The Reviews are intended to provide independent, comprehensive and comparative assessments of OECD member and non-member countries' tax systems as well as concrete recommendations for tax policy reform. This report provides a comprehensive assessment of Lithuania's tax and benefit system and recommendations for tax reform. It outlines the country's key economic and tax challenges and assesses the effects of taxation on employment. A special focus is given to the taxation of self-employed individuals